Augmented reality (AR) and virtual reality (VR) applied in dentistry - Huang, Ta-Ko; Yang, Chi-Hsun; Hsieh, Yu-Hsin; Wang, Jen-Chyan; Hung, Chun-Cheng (The Kaohsiung journal of medical sciences, 2018)
The OSCE is a reliable evaluation method to estimate the preclinical examination of dental students. The most ideal assessment for OSCE is used the augmented reality simulator to evaluate. This literature review investigated a recently developed in virtual reality (VR) and augmented reality (AR) starting of the dental history to the progress of the dental skill. As result of the lacking of technology, it needs to depend on other device increasing the success rate and decreasing the risk of the surgery. The development of tracking unit changed the surgical and educational way. Clinical surgery is based on mature education. VR and AR simultaneously affected the skill of the training lesson and navigation system. Widely, the VR and AR not only applied in the dental training lesson and surgery, but also improved all field in our life.